2016
DOI: 10.1111/clr.12787
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical and radiographic status of platform‐switched implants placed in patients with and without type 2 diabetes mellitus: a 24‐month follow‐up longitudinal study

Abstract: Platform-switched implants can remain clinically and radiographically stable in patients with T2DM in a manner similar to non-diabetic individuals. However, it is emphasized that bone loss around implants is influenced by several factors (such as oral hygiene status, glycemic control and tobacco smoking) and not merely platform switching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 23 publications
1
30
0
1
Order By: Relevance
“…Upon exclusion of reports deemed ineligible based on their 401 titles and abstracts, 74 studies remained for full‐text evaluation. Finally, 62 studies were excluded for not meeting the inclusion criteria (Table ), leaving 12 studies eligible for inclusion in the qualitative analyses (Aguilar‐Salvatierra et al., ; Al Amri & Abduljabbar, ; Al Amri, Abduljabbar, Al‐Kheraif, Romanos, & Javed, ; Al Amri et al., ; de Araujo Nobre, Malo, & Antune, ; Dalago, Schuldt Filho, Rodrigues, Renvert, & Bianchini, ; Daubert, Weinstein, Bordin, Leroux, & Flemming, ; Erdogan et al., ; Ferreira, Silva, Cortelli, Costa, & Costa, ; Konstantinidis, Kotsakis, Gerdes, & Walter, ; Marrone, Lasserre, Bercy, & Brecx, ; Renvert, Aghazadeh, Hallström, & Persson, ) (Figure ; Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Upon exclusion of reports deemed ineligible based on their 401 titles and abstracts, 74 studies remained for full‐text evaluation. Finally, 62 studies were excluded for not meeting the inclusion criteria (Table ), leaving 12 studies eligible for inclusion in the qualitative analyses (Aguilar‐Salvatierra et al., ; Al Amri & Abduljabbar, ; Al Amri, Abduljabbar, Al‐Kheraif, Romanos, & Javed, ; Al Amri et al., ; de Araujo Nobre, Malo, & Antune, ; Dalago, Schuldt Filho, Rodrigues, Renvert, & Bianchini, ; Daubert, Weinstein, Bordin, Leroux, & Flemming, ; Erdogan et al., ; Ferreira, Silva, Cortelli, Costa, & Costa, ; Konstantinidis, Kotsakis, Gerdes, & Walter, ; Marrone, Lasserre, Bercy, & Brecx, ; Renvert, Aghazadeh, Hallström, & Persson, ) (Figure ; Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Upon further scrutiny, three prospective cohort studies were excluded from the quantitative synthesis as they were highly heterogeneous compared to the rest of the reported data as the authors reported only on successful implants and the three reports also seem to represent possible data overlap (Al Amri & Abduljabbar, ; Al Amri et al., , ). Consequently, of the 12 studies included in qualitative analysis, nine could be synthesized based on their OR or RR for having mucositis and/or peri‐implantitis (Aguilar‐Salvatierra et al., ; de Araujo Nobre et al., ; Dalago et al., ; Daubert et al., ; Erdogan et al., ; Ferreira et al., ; Konstantinidis et al., ; Marrone et al., ; Renvert et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maintenance of crestal bone level around dental implants at the implant/abutment junction (IAJ) plays an essential role in the overall success of dental implant therapy . Exposure of implant surfaces due to early crestal bone loss (CBL) facilitates the accumulation and proliferation of pathogenic microbes on implant surfaces .…”
mentioning
confidence: 99%
“…The other three studies were excluded due to the highest risk of bias. Further, only six studies reported MBL …”
Section: Resultsmentioning
confidence: 99%